3D Bioprinting Pluripotent Stem Cell Derived Neural Tissues Using a Novel Fibrin Bioink Containing Drug Releasing Microspheres - Sharma, Ruchi; Smits, Imke P. M.; De La Vega, Laura; Lee, Christopher; Willerth, Stephanie M. (Frontiers in Bioengineering and Biotechnology, 2020)
3D bioprinting combines cells with a supportive bioink to fabricate multiscale, multi-cellular structures that imitate native tissues. Here, we demonstrate how our novel fibrin-based bioink formulation combined with drug releasing microspheres can serve as a tool for bioprinting tissues using human induced pluripotent stem cell (hiPSC)-derived neural progenitor cells (NPCs). Microspheres, small spherical particles that generate controlled drug release, promote hiPSC differentiation into dopaminergic neurons when used to deliver small molecules like guggulsterone. We used the microfluidics based RX1 bioprinter to generate domes with a 1 cm diameter consisting of our novel fibrin-based bioink containing guggulsterone microspheres and hiPSC-derived NPCs. The resulting tissues exhibited over 90% cellular viability 1 day post printing that then increased to 95% 7 days post printing. The bioprinted tissues expressed the early neuronal marker, TUJ1 and the early midbrain marker, Forkhead Box A2 (FOXA2) after 15 days of culture. These bioprinted neural tissues expressed TUJ1 (15 ± 1.3%), the dopamine marker, tyrosine hydroxylase (TH) (8 ± 1%) and other glial markers such as glial fibrillary acidic protein (GFAP) (15 ± 4%) and oligodendrocyte progenitor marker (O4) (4 ± 1%) after 30 days. Also, quantitative polymerase chain reaction (qPCR) analysis showed these bioprinted tissues expressed TUJ1, NURR1 (gene expressed in midbrain dopaminergic neurons), LMX1B, TH, and PAX6 after 30 days. In conclusion, we have demonstrated that using a microsphere-laden bioink to bioprint hiPSC-derived NPCs can promote the differentiation of neural tissue.